Prevalence and associated factors of comorbid anxiety disorders in late-life depression: Findings from geriatric tertiary outpatient settings - Chawisa Suradom (2019)
© 2019 Suradom et al. Purpose: The study evaluated the prevalence of comorbid anxiety disorders in late-life depression (LLD) and identified their associated factors. Patients and methods: This study involved 190 elderly Thais with depressive disorders diagnosed according to the Mini-International Neuropsychiatric Interview (MINI). Anxiety disorders were also diagnosed by the MINI. The 7-item Hamilton Depression Rating Scale (HAMD-7), Montreal Cognitive Assessment, Geriatric Depression Scale (GDS), Core Symptoms Index, Neuroticism Inventory, Perceived Stress Scale and Multidimensional Scale for Perceived Social Support were completed. Descriptive statistics and ORs were used for analysis. Results: Participants included 139 females (73.2%) with a mean age of 68.39±6.74 years. The prevalence of anxiety disorders was 7.4% for generalized anxiety disorder (GAD), 4.7% for panic disorder, 5.3% for agoraphobia, 1.1% for social phobia, 2.1% for obsessive–compulsive disorder and 3.7% for post-traumatic stress disorder, with an overall prevalence of 16.84%. The comorbidity of anxiety disorders was associated with gender (P=0.045), history of depressive disorder (P=0.040), family history of depressive disorder (P=0.004), GDS (P=0.037), HAMD-7 (P=0.001), suicidality (P=0.002) and neuroticism (P=0.003). History of alcohol use was not associated. Conclusion: The prevalence of anxiety in LLD was comparable to other studies, with GAD and agoraphobia being the most prevalent. This study confirmed the role of depression severity and neuroticism in developing comorbid anxiety disorders.